Atlas of Normal Microanatomy, Procedural and Processing Artifacts, Common Background Findings, and Neurotoxic Lesions in the Peripheral Nervous System of Laboratory Animals. (January 2020) - Pardo, Ingrid D.; Weber, Klaus; Cramer, Sarah; Krinke, Georg J.; Butt, Mark T.; Sharma, Alok K.; Bolon, Brad
The ability to differentiate among normal structures, procedural and processing artifacts, spontaneous background changes, and test article–related effects in the peripheral nervous system (PNS) is essential for interpreting microscopic features of ganglia and nerves evaluated in animal species commonly used in toxicity studies evaluating regulated products and chemicals. This atlas provides images of findings that may be encountered in ganglia and nerves of animal species commonly used in product discovery and development. Most atlas images are of tissues from control animals that were processed using routine methods (ie, immersion fixation in neutral-buffered 10% formalin, embedding in paraffin, sectioning at 5 µm, and staining with hematoxylin and eosin) since these preparations are traditionally applied to study materials produced during most animal toxicity studies. A few images are of tissues processed using special procedures (ie, immersion or perfusion fixation using methanol-free 4% formaldehyde, postfixation in glutaraldehyde and osmium, embedding in hard plastic resin, sectioning at 1 µm, and staining with toluidine blue), since these preparations promote better stabilization of lipids and thus optimal resolution of myelin sheaths. Together, this compilation provides a useful resource for discriminating among normal structures, procedure- and processing-related artifacts, incidental background changes, and treatment-induced findings that may be seen in PNS tissues of laboratory animals.